Oral Communication Needs of Pre-Service Teachers in Practice Teaching - Cristie Ann L. Jaca; Felino B. Javines (Randwick International of Education and Linguistics Science Journal, 2020)
Practice teaching is the culmination of the teacher education program where student teachers apply learned content knowledge and pedagogical skills in real classroom teaching. The purpose of this paper is to present the perceived oral communication needs of student teachers during their practice teaching. Survey questionnaire, classroom observations and focused group discussions were used to collect the needed data. It was found that student teachers’ oral communication skills in English fall short and need to be enhanced to cope with the demands of the teaching profession. Likewise, it was noted that the need to have a special kind of English class for pre-service teachers is very much needed to help them in their practice teaching since the medium of instruction used in class is English. Furthermore, the kind of English they need for classroom communication is also very specific for classroom interactions. The findings serve as basis in designing a module that can be used in remedial class in English for Pre-Service Teachers to respond to their communicative needs in the classroom.